Hydrodynamic correlations in isotropic fluids and liquid crystals simulated by multi-particle collision dynamics - Híjar, H. (Condensed Matter Physics, 2019)
Multi-particle collision dynamics is an appealing numerical technique aiming at simulating fluids at the mesoscopic scale. It considers molecular details in a coarse-grained fashion and reproduces hydrodynamic phenomena. Here, the implementation of multi-particle collision dynamics for isotropic fluids is analysed under the
so-called Andersen-thermostatted scheme, a particular algorithm for systems in the canonical ensemble. This
method gives rise to hydrodynamic fluctuations that spontaneously relax towards equilibrium. This relaxation
process can be described by a linearized theory and used to calculate transport coefficients of the system. The
extension of the algorithm for nematic liquid crystals is also considered. It is shown that thermal fluctuations
in the average molecular orientation can be described by an extended linearized scheme. Flow fluctuations
induce orientation fluctuations. However, orientational changes produce observable effects on velocity correlation functions only when simulation parameters exceed their values from those used in previous applications
of the method. Otherwise, the flow can be considered to be independent of the orientation field. Динамiка багаточастинкових зiткнень — це зручна числова методика для моделювання плинiв на мезоскопiчних масштабах. Вона дає змогу розглядати молекулярнi деталi в огрублений спосiб i вiдтворювати
гiдродинамiчнi явища. У данiй статтi, застосування динамiки багаточастинкових зiткнень до iзотропних
плинiв проаналiзовано за так званою термостатованою схемою Андерсена, конкретного алгоритма для
систем у канонiчному ансамблi. Цей метод виявляє гiдродинамiчнi флуктуацiї, якi спонтанно релаксують
до рiвноваги. Цей релаксацiйний процес можна описати з допомогою лiнеаризованої теорiї та використати для обчислення коефiцiєнтiв переносу в системi. Також розглянуто розширення алгоритму на нематичнi рiдкi кристали. Показано, що тепловi коливання середньої орiєнтацiї молекули можна описати за
допомогою розширеної лiнеаризованої схеми. Флуктуацiї потоку iндукують орiєнтацiйнi флуктуацiї. Проте, орiєнтацiйнi змiни мають помiтний вплив на кореляцiйнi функцiї швидкостей тiльки, коли параметри
моделювання перевищують їх значення у порiвняннi зi значеннями, що використовуються у попереднiх застосуваннях методу. В протилежному випадку, даний потiк можна вважати незалежним вiд поля
орiєнтацiї.